2001
DOI: 10.1007/s002640000199
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the healing of tendon autograft and tendon-bone autograft using patellar tendon in rabbits

Abstract: In order to compare the healing of tendon to bone and the healing of bone to bone in a rabbit model, the lateral 4 mm of patellar tendons were detached from their insertion into the tibia either subperiosteally (group I) or with a bone block (group II) and implanted into drill holes in the proximal articular surface of the tibia. The histological and biomechanical features of the graft incorporation were observed at 2, 4, 8 and 12 weeks. Histological patterns similar to normal tendon-bone attachment were seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 10 publications
2
63
0
Order By: Relevance
“…Another disadvantage to using hamstrings tendon grafts is that soft-tissue to bone healing takes longer than bone-to-bone healing and is less reliable. 15 Soft tissue grafts may also have a propensity to cause tunnel widening. 16 However, there is little evidence that tunnel widening affects clinical or arthrometric outcomes following ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Another disadvantage to using hamstrings tendon grafts is that soft-tissue to bone healing takes longer than bone-to-bone healing and is less reliable. 15 Soft tissue grafts may also have a propensity to cause tunnel widening. 16 However, there is little evidence that tunnel widening affects clinical or arthrometric outcomes following ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Several animal models have shown a slower incorporation rate into the bone tunnel with soft-tissue grafts compared to bone-plug grafts such as bone-patellar tendonbone (BTB) [73,74,81,105].…”
Section: Autograftmentioning
confidence: 99%
“…In the bone-to-bone tunnel, the bone plug showed complete incorporation at 6 weeks; however, in the tendon-bone tunnel-though there were some Sharpey 0 s like fibers-graft incorporation was incomplete. A rabbit model study found that the healing of bone-to-bone was mature at 8 weeks, whereas the healing of tendon-to-bone was mature at 12 weeks [74]. Although different animal models were used, the similarity of results in the aforementioned studies indicates that soft-tissue graft is slower to incorporate than bone-plug graft (Fig.…”
Section: Autograftmentioning
confidence: 99%
“…Average age = 23.7 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) years. The left knee was involved 6 times and the right knee 12 times.…”
Section: Methodsmentioning
confidence: 99%